Measurements of the pp → WZ inclusive and differential production cross sections and constraints on charged anomalous triple gauge couplings at √s = 13 TeV; Journal of High Energy Physics; Vol. 2019, iss. 5 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen